Sociodemographic and environmental factors associated with diarrhoeal illness in children under 5 years in Uganda, 2016: a cross-sectional study - Nathan Ssekandi; Nonhlanhla Tlotleng; Nisha Naicker (BMC Infectious Diseases, 2023)
Abstract Background Uganda is among the 10 countries in the sub-Saharan Africa region that have the highest prevalence of diarrhoeal disease. Evidence suggests that the severity of childhood diarrhoeal disease is escalated through various sociodemographic and environmental factors. Objectives To assess prevalence of diarrheal illness in children below the age of 5 years in Uganda in 2016 and associated factors. Methods A cross-sectional study was employed that analyzed secondary data from the 2016 Uganda Demography and Health Surveys. Children with and without diarrhea were compared. A logistic regression was used to determine sociodemographic and environmental factors associated with diarrheal illness in children with statistical significance at p < 0.05. Results The prevalence of childhood diarrhoeal illness for children below the age of 5 years in Uganda was 20.9% (n = 2838/13,753). There was a statistically significant difference when comparing children diarrhoeal with the following sociodemographic factors: caregiver’s age, child’s age and gender and duration of breastfeeding (p < 0.0001). Children with a caregiver aged between 15 and 24 years (aOR;1.42; 95% CI:1.24–1.62) and 25–34 years (aOR;1.19; 95% CI:1.04–1.37) were more likely to report diarrhoeal disease, compared to those with a caregiver aged 35–49 years. For environmental factors, households using springs water, access to health facility and children who received a dose of vitamin A had a decreased risk of reporting children diarrhoeal. Conclusion Significant factors in the study like caregiver’s age, gender and duration of breastfeeding will create the opportunity for all interventions to shift their focus to these factors thus a better evidence-based approach to reducing of diarrhoeal disease will be achieved in the country.